Demographic Differences in Insomnia and Anxiety and the Association with Cardiovascular Risk Factors among Jordanian Healthy Adult - Ahmed Mohammad Al-Smadi; Abedalmajeed Shajrawi; Omar Salem Gammoh; Ala Ashour; Loai Issa Tawalbeh; Eman Harb; Hanan Esmadi; Hekmat Yousef Al-Akash (Wolters Kluwer Medknow Publications, 2024)
Background: Prior studies showed that anxiety and insomnia are both associated with Cardiovascular Disease (CVD). There is a lack of literature related to the prevalence of insomnia and anxiety among healthy adult populations in developing countries as in Jordan, Therefore, this study aimed to examine the association between the CVD risk factors and both insomnia and anxiety among healthy adults had one or more modifiable CVD risk factors. Materials and Methods: A cross-sectional method was used to examine the prevalence of anxiety, insomnia, and demographical and clinical association with anxiety and insomnia among 1000 Jordanian adult participants using the Hamilton Anxiety Rating Scale and the insomnia severity index. Pearson's correlation was used to examine the correlation between anxiety and insomnia scores. Linear regression was used to examine predictors to anxiety and insomnia based on demographical and clinical details. Results: The result of the current study showed that (30.20%) of participants had higher anxiety scores, (29.70%) had moderate to severe insomnia. Moreover, there was a significant positive correlation between anxiety and insomnia scores, p = 0.01. Based on the current study findings only marital status and anxiety were unique predictors of insomnia F(14,45) = 989, p = 0.001. Moreover, Predictors of anxiety were gender, hypertension, Diabetes mellitus, dyslipidemia, and insomnia F(19,89) = 989, p = 0.001. Conclusions: Sleep and psychological well-being are important components of an adult's health and well-being. The study showed that marital status and anxiety are predictors of insomnia. Whereas, gender, hypertension, diabetes mellitus, dyslipidemia, and insomnia were predictors of anxiety. This study highlights the importance of the implementation of a primary prevention strategy for individuals with modifiable CVD risk factors to reduce anxiety and insomnia levels among adults.